PEMBELAJARAN COOPERATIVE LEARNING TYPE STAD DALAM MENINGKATKAN HASIL BELAJAR - daman Huri; Jamiluddin Yacub; Ahmad Ardiansyah; Siti kholijah (JPPG : Jurnal Pengembangan Profesi Guru, 2023)
The application of Tpye STAD cooperative learning to students in Class X with learning material for the teacher professional code of ethics course using hand out media went well in the implementation of student discussions individually and in groups, these activities were proven to be able to increase student learning activities. Student compliance and enthusiasm in learning using the Tye STAD cooperative learning approach is proven to increase student study results. The student learning process is more interesting because the lecturer involves all students in the discussion process so that the activities and student learning outcomes. Lecture material to be discussed has been given to students in advance, so that students have complete and in-depth materials and references in learning, thus students will get competitive knowledge and have a complete basis. Students will get complete knowledge because in the learning process because in the process the knowledge gained is not to be memorized but to be scrutinized, criticized. Results and learning activities that are taught with media handouts that contain problems that are solved individually and in groups can improve student learning outcomes. The use of hand out media in the cooperative type stad method is very capable of fostering students' thinking skills and awareness in seeking, observing and finding solutions to the problems given